Beyond physical ability—predicting women’s football performance from psychological factors - Pettersen, Susann Dahl; Martinussen, Monica; Handegård, Bjørn Helge; Rasmussen, Lene-Mari Potulski; Koposov, Roman; Adolfsen, Frode (Frontiers in Psychology, 2023)
Even though there is a clear agreement among researchers that psychological factors are a vital part of a football player’s performance, the topic has not been investigated thoroughly. The present study aimed to examine the predictive value of psychological factors on female football players' match performance. A sample of 156 players from the top two leagues in Norway completed the following questionnaires: Perceived Motivational Climate in Sport Questionnaire 2 (PMCSQ-2), Big Five Inventory (BFI-20), Self-Regulated Learning questionnaire, Grit-S and Sport Mental Toughness Questionnaire (SMTQ). Match performance data was collected from the online database of the performance analysis company InStat. Results from a linear mixed model analysis showed that perceived mastery climate and extraversion were the only significant predictors of performance. Other relevant indicators such as mental toughness, self-regulated learning, and grit, did not predict performance. These findings suggest that the team climate facilitated by coaches may be more important for predicting match performance than individual psychological factors.